Antecedentes da lealdade dos clientes em trocas transacionais: um estudo no setor varejista farmacêutico - Luiz Antonio de Carvalho Godinho (2004)
Relationship Marketing is a subject already comprehensively studied that lately has raised interest also in managers of the marketing field. When speaking of relationship marketing, it is mandatory to bring up the concept of loyalty and how it is formed. The variables that influence the formation of loyalty and how they are related have been objects of analysis for a long time, when considering the creation of relationshipsbetween companies and its clients. The present work aims to analyze the validity of a model that takes into consideration the quality perceived by the client, the value perceived by the client, satisfaction and trust as the variables influencing the formation of loyalty in the relationship betweencompanies and clients. In order to do so, a conclusive descriptive research was carried out, through a questionaire applied to a sample of 602 interviewees. The participants were clients in three stores of one of the largest farmaceutical companies in Minas Gerais, situated in the metropolitan area of Belo Horizonte. The results found indicate that, in the researched stores, the model is valid. However, the model presents itself with a better adjustment when the direct relation between value perceived by the clients and loyalty is not considered. It is also worth stressing thefinding of a strong influence of the variable satisfaction and the formation of loyalty by the clients.